Policy Implementation of the Community-Based Intervention (IBM) Program BNN Central Kalimantan Province - Rambang, Alphaomega Pulcherima; Purbosari, Nita Ryan; Bernardianto, Raden Biroum; Koesanto, Stefani Made Ayu Artharini (Yayasan Ilomata, 2024)
Community-Based Intervention (IBM) is one of the programs for the Prevention of Eradication of Narcotics Abuse and Illicit Trafficking with the concept of community empowerment (from the community, by the community, and for the community). These programs aim to intervene in light drug abusers by people who have been trained by the National Narcotics Agency and have competence. BNNP Central Kalimantan started implementing the Community-Based Intervention Program in 2021 where there are several obstacles in its implementation. This study aims to produce recommendations and strategies so that the Community-Based Intervention program at BNNP Central Kalimantan can run optimally. This research used qualitative research methods. The data was analyzed using the Interactive analysis model of Miles, Huberman, and Saldana. The research results indicate that the variables that require attention and serve as preconditions for the success of the implementation process have been met in the implementation of the IBM. As for the constraints still encountered, they will serve as recommendations for the sustainability of future programs